(untitled) (Italian Review of Legal History, 2021)
In Giangastone Bolla’s Program for the Review of Agricultural Law (1922) land ownership was a testing ground for the «modern transformations of property law» – on which Enrico Finzi – primarily with the «social function». Bolla observed the shift from ownership to the company; asserted that the link between agriculture and the state required the scholar of agricultural law to undertake the «social and economic reconstruction of the country». In view of the «social function» Arrigo Serpieri – since 1923 Undersecretary of State for Agriculture – promoted various legislative measures for the «integral reclamation»; the policy for agriculture was linked to the organization of the corporate state in fieri (Brugi, Arcangeli). The 1933 Consolidated Law (TU) aimed at the rehabilitation of the land to increase its productivity and improve the conditions of the peasants with land transformations of public interest, with possible expropriation of large estates and forced execution of reclamation works on private lands; from 1946 the Consolidated Law of 1933 will be considered an indication for the agrarian reform (Rossi Doria, Segni). In the first Congress of Agricultural Law, (Florence 1935), Maroi, Pugliatti, Serpieri, D’Amelio, Bolla, Ascarelli, Calamandrei discussed some issues, in the first place agricultural law as a factual experience, linked to rural life, irreducible to a uniform juridical order; hence the ‘long duration’ of the Jacini Report on the various agricultural Italy. In view of the civil codification, the jurists noted the insufficiency of the individualistic system; placed the request for rules focused on the good and not on the subjects, up to the overcoming of the distinction between public and private law. The most illustrious Italian jurists intervened in the volume promoted by the Confederation of agricultural workers; The Fascist conception of property expressed the detachment from the liberal conception – with an emphasis on land ownership based on work (Ferrara, Panunzio) – and held firm to private initiative (Filippo Vassalli). Bolla reiterated the particularity of land ownership between the corporate system and the civil code project, «a private institution, aided and regulated by the State», with the owner «moderator et arbiter» of his own initiative. In the civil code of 1942, land ownership made sense of the dynamic aspect of productive activity, without contemplating the «social function» as a «new property right» (Pugliatti, Vassalli, D’Amelio). After the fall of the fascist regime, the struggles in the countryside forced Minister Gullo to plan agrarian contracts and regulate the occupation of uncultivated lands, with multiyear concessions to the occupying peasants; the De Gasperi award compensated the sharecroppers. The different economies of the ‘different agrarian Italy’ did not recommend a uniform agrarian reform; the reorganized political parties aimed at the distribution of expropriated lands, compensation to the private owner, without damaging the right of ownership. The initial action of the State to erode the large estates, with special reform bodies, had as its purpose the enhancement of small peasant property (Segni, Bandini). To combine private property and social interest in Constitution, Mortati motivated his proposal for a «constitutional statute»; Fanfani asked for «an article that speaks expressly of the land». The large estate was the most urgent but divisive issue, between Di Vittorio, who asked for its «abolition», and Einaudi for its «transformation», a choice that was imposed in the name of the various ‘rural Italy’; the proposal for a rule intended to hinder large landholdings was not accepted. Article 44 of the Constitution provided for a law to impose «obligations and constraints on private land ownership», in order to «achieve rational land use and fair social relations». Bolla appreciated the choice of «transforming individual property into social property»; Vassalli wrote about a non-original «handbook for resolving the agrarian problem». In the project of the Minister for Agriculture Segni – who managed to launch a contested agrarian reform – art. 44 dictated tasks to the «future legislator»; the Sila law of 21 May 1950, the excerpt law of 21 October 1950 for particularly depressed areas, the bills on agricultural contracts were discussed in the Third Congress of Agricultural Law and in the first International Conference, promoted by Bolla, with interventions by Bassanelli, Segni, Capograssi, Pugliatti, Santoro Passarelli, Mortati, Esposito. Work was considered the architrave of land ownership, «a continually changing right, which must be modeled on social needs» (Bolla). In this context, the theoretical-practical, juridical-political reflection of Mario Bracci, professor of administrative law in Siena, rector, also in charge of teaching agricultural law, is interesting. Representative of the PdA at the National Council in the Agriculture Commission, Bracci proposed to write a «book on the socialization of the land», never published; the personal archive offers a wealth of notes previously unpublished on the subject. Bracci defined land ownership as the lintel of agricultural law and a crossroads of private and public law, between land reclamation laws, civil codification, art. 44 of the Constitution, the agrarian reform, understood as a «problem of justice». From Fascism to the Republic, Bracci grasped technical continuities and ideological discontinuities in the structure of landed property, considered to be of constitutional significance, in referring to the person, «the conditions of the person are inextricably linked to those of landed property». As a scholar and professor of administrative law and agricultural law, since July 1944 Bracci intended to respond to the conflict in the countryside, mediating between «public purposes of agricultural production and the needs of social justice»; proposed «adequate legal forms which are forms of public law».